Influence of conjunctions on modal semantics of conditional hypothetic forming (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the peculiarities of functioning of the conjunctions in the structure of complex sentences with inferior conditional part on material of Ukrainian. The modification of categorical semantics of hypothetic depending upon the choice of conjunctions, which are manifestations of unreal semantic and syntactic relations, has been investigated.
Keywords: the semantics of conditional hypothetic; the conjunctions of condition; subjunctive mood; complex sentence with subordinate conditional part; the semantics of hypothetic; the unreal semantic and syntactic relations of unreal condition